External validation of preoperative and postoperative nomograms for prediction of cancer‐specific survival, overall survival and recurrence after robot‐assisted radical cystectomy for urothelial carcinoma of the bladder. (22nd January 2014) - Al‐Daghmin, Ali; English, Stephen; Kauffman, Eric C.; Din, Rakeeba; Khan, Aabroo; Syed, Johar R.; Sztorc, Jenna; Mehedint, Diana; Sharif, Mohammad; Shi, Yi; Wilding, Gregory; Guru, Khurshid A.
<x xml:space="preserve">Abstract</x> Objective To externally validate currently available bladder cancer nomograms for prediction of all‐cause survival (ACS), cancer‐specific survival (CSS), other‐cause mortality (OCM) and progression‐free survival (PFS). Patients and Methods Retrospective analysis of a prospectively maintained database of 282 patients who underwent robot‐assisted radical cystectomy (RARC) at a single institution was performed. The Bladder Cancer Research Consortium (BCRC), International Bladder Cancer Nomogram Consortium (IBCNC) and Lughezzani nomograms were used for external validation, and evaluation for accuracy at predicting oncological outcomes. The 2‐ and 5‐year oncological outcomes were compared, and nomogram performance was evaluated through measurement of the concordance (c‐index) between nomogram‐derived predicted oncological outcomes and observed oncological outcomes. Results The median (range) patient age was 70 (36–90) years. At a mean follow‐up of 20 months, local or distant disease recurrence developed in 30% of patients. With an overall mortality rate of 33%, 17% died from bladder cancer. The actuarial 2‐ and 5‐year PFS after RARC was 62% (95% confidence interval [CI] 54–68) and 55% (95% CI 46–63), respectively. The actuarial 2‐ and 5‐year ACS was 66% (95% CI 59–72) and 47% (95% CI 37–55), respectively, and the 2‐ and 5‐year CSS was 81% (95% CI 74–86) and 67% (95% CI 57–76), respectively. The PFS c‐index for IBCNC was 0.70 at 5 years, and for BCRC was 0.77 at both the 2 and 5 years. The accuracy of ACS and CSS prediction was evaluated using the BCRC and Lughezzani nomograms. Using the BCRC nomogram, c‐indices of for 2‐ and 5‐year ACS were each 0.73 and c‐indices for 2‐ and 5‐year CSS were 0.70 each. The performance of Lughezzani nomogram for 5‐year ACS, cancer‐specific mortality and OCM were 0.73, 0.72 and 0.40, respectively. The BCRC nomogram prediction of advanced pathological stage and lymph node metastasis was modest, with c‐indices of 0.66 and 0.61, respectively. Conclusions Bladder cancer nomograms available from the current open RC literature adequately predict ACS, CSS and PFS after RARC. However, prediction of advanced tumour stage and lymph node metastasis was modest and the Lughezzani nomogram failed to predict OCM.